Migração interna e deslocamento forçado: análise do padrão migratório colombiano do final do século XX e começo do século XXI - Sulma Marcela Cuervo Ramirez (2014)
Migratory trajectories conform a form of historical "footprint" of society, through which are spatially reveals the order that society followed for their process economic and social production. The way are gives articulation between these economic and social factors and these migratory trajectories in a particular historical context, is the migratory pattern. Under this premise, this study has as fundamental purpose check whether there is indeed a pattern of internal migration in the Colombian case, we seek to evaluate the behavior of internal migration as part of the economic, productive and social transformations that Colombia experienced in the late twentieth century and early twenty-first century, in situations of political and armed conflict. To achieve this purpose, the demographic census micro data for 1993 and 2005, provided by the National Administrative Department of Statistics are analyzed - DANE; and the Unified Registry of Displaced Population Information Network National Victims of the Armed Conflict in Colombia RUPDs-INR, available for the period 1985 -. 2014 The concept that is adopted as migrant refers to the individual who resided five years ago in a municipality other than the municipality of registration, regardless of their place of birth; and that survives death and re-emigration. In the case of forced displacement, we consider the cumulative events annually, regardless of whether they were experienced by the same person, and it occurred inside or outside the municipal boundaries. The data analysis and the application of techniques for the estimation of migration and multivariate analysis allowed the detection of one hand, spatial regularities that arise from migratory exchanges in space and on the other, that the pattern of internal migration Colombian articulate and overlap two migratory trajectories markedly selective systems. The first system corresponds to the migratory trajectories of intra-regional order, derived from the parsimonious industrialization process started in the nineteenth century and consolidated in the second half of the twentieth century, and which constitute the major cities and their metropolitan areas. This system are dominated by inter-urban migratory trajectories, but still articulated with traditional areas of expulsion, which also underpin flows of rural origin. A second migratory system arise in areas historically excluded of the paths of industrialization, where has recently been expanded agricultural frontier for agribusiness and oil exploration. In these areas are configured conditions for the production and marketing of illicit businesses in which peasant populations are hinged or rejected in different ways. This process ends up sustaining migratory flows from rural areas to two types of borders: those surrounding the consolidated urban areas, and those that make the marginal corridors in the areas of international border. The various migratory, dominant and secondary trajectories, that are configured on both migration systems reproduce the structural factors of spatial inequity present in Colombian geography, and, from them, the selectivity for migration. For example, streams that originate in urban areas are dominated by more educated adults; but those who emerge from rural areas to the boundaries, by young adults with low education. The theoretical framework of migration, derived from neoclassical macroeconomics, with the model Equilíbrio; and the structuralist school, with the Center-Periphery Model and the Theory of Global Systems, explains a fragmented manner different historical moments of the evolution of the migratory pattern of the Colombian case, particularly for the second half of the twentieth century. For this new century, are necessary analytical frameworks that consider, beyond the economic dimension, political and social factors that contribute to the better understanding of the dynamics of expulsion in forced condition within and beyond national boundaries. The changes in migration pattern between the late twentieth century and early twenty-first century is characterized by a decrease in the volume of internal migration voluntary and increase in forced displacements of character, domestic and international, but that are not captured in censuses. Between the two periods have widened distances migratory between origins and destinations, and there are new areas for migratory influences that complement the rays of action for all migration and strengthen systems intra-regional migratory exchanges, dominated by women and young adults.